Fostering work engagement via islamic work ethic and quality of work-life: the mediating role of psychological capital/ Mohd Azrul Azman, Shafiq Shahruddin and Muhammad Aiman Arifin - Azman, Mohd Azrul; Shahruddin, Shafiq; Arifin, Muhammad Aiman (Universiti Teknologi MARA Selangor, 2022)
In the modern economy of industry organization 4.0, the lack of employee engagement among multigenerational employees is one of the concerns for most employers. The issue is mostly about ethical misconduct and quality of work in the workplace whereby there is a need to stimulate discussion further through psychological capital. The objective and purpose of this study are to expand the literature and framework on employee engagement by examining the role of IWE and QWL, and the factors that would enhance the needs of employee engagement through psychological mediators. The current study suggests that psychological capital mediates the relationship between IWE, QWL, and employee engagement as the organizational approach needs to be broader in approaching the new framework according to the passage of time. Therefore, the presented model will be proposed to the private sectors based on the need as the key main industry in Malaysia. The importance of employee engagement is to develop the economic sustainability of the country while at the same time reducing the cost of retention among new generation employees.